Effects of levels of concentrate supplementation on milk production and body weights of lactating dairy cows - Biwott, K.J.; Kaitho, R.; Gachuiri, C.K.; Wahome, R.G.; Tanner, J.C. (International Livestock Research Institute, 1998)
Nineteen dairy cows were used over a 7-month period to evaluate the effect of allocating different levels of concentrate during early lactation. The animals were fed on grass hay basal diet and supplemented with either 2 Kg (LLC), 4 Kg (MLC) or 8 Kg (HLC) per day. Milk yields were measured daily, body weight and body condition scores were monitored weekly. Milk yields during the first 12 weeks of lactation were 11.6, 12.6 and 16.9 Kg/day for LLC, MLC and HLC respectively. The HLC had significantly higher (P<0.001) milk yield than both MLC and LLC. The body weights and condition scores of animals in different treatment groups remained relatively constant during the study period. The HLC were significantly heavier than the other two groups.